Procedings of the British Machine Vision Conference 2006 2006
DOI: 10.5244/c.20.37
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Training of Hyper-feature Models for Object Identification

Abstract: Object identification is the task of identifying specific objects belonging to the same class such as cars. We often need to recognize an object that we have only seen a few times. In fact, we often observe only one example of a particular object before we need to recognize it again. Thus we are interested in building a system which can learn to extract distinctive markers from a single example and which can then be used to identify the object in another image as "same" or "different".Previous work by Ferencz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Recently there has been considerable interest for face and visual identification [5,8,12,15,20,24]. Faces are particularly challenging due to possible variations in appearance, see for example Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been considerable interest for face and visual identification [5,8,12,15,20,24]. Faces are particularly challenging due to possible variations in appearance, see for example Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The toy cars dataset The Jain faces dataset [12] is a subset of "Faces in the news" 2 and contains 500 positive and 500 negative pairs of faces, and we measure our accuracy like the authors by 10 fold cross validation. That dataset is built from faces sampled "in the news", hence there are very large differences of resolution, light, appearance, expression, pose, noise, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the magenta X at 4.3 patches and 1.02% error shows the performance of the cascade model ample classification results. As part of an extension of this current paper (Jain et al 2006), we have also compared this algorithm to Bayesian face recognition (Moghaddam et al 2000), which won the 1996 FERET face identification competition, and found our algorithm to perform significantly better on this difficult data set. Our more recent work further improves on the results reported here by training a discriminative model on top of the hyper-features.…”
Section: Facesmentioning
confidence: 99%